A Decade Long Slowdown in Road Crashes and Inherent Consequences Predicted for South Africa - Machetele, Dimakatso; Yessoufou, Kowiyou (Frontiers in Future Transportation, 2021)
Globally, there are 1.35 million road fatalities every year, which are estimated to cost governments approximately US$ 518 billion, making road fatalities the eighth leading cause of death across all age groups and the leading cause of death of children and young adults. In South Africa, despite tremendous governmental efforts to curb the soaring trajectory of road crashes, the annual number of road fatalities has increased by 26% in recent years. By fitting a structural equation model (SEM) and a GARCH Model (Generalized Auto-Regressive Conditional Heteroskedasticity) to analyze and predict future trend of road crashes (number of road crashes, number of casualties, number of fatal crashes and number of persons killed) in South Africa, we propose and test a complex metamodel that integrates multiple causality relationships. We show an increasing trend of road crashes over time, a trend that is predictable by number of vehicles in the country, the population of the country and the total distance travelled by vehicles. We further show that death rate linked to road crashes is on average 23.14 deaths per 100,000 persons. Finally, in the next decade, the number of road crashes is predicted to be roughly constant at 617,253 crashes but can reach 1,896,667 crashes in the worst-case scenario. The number of casualties was also predicted to be roughly constant at 93,531 over time, although this number may reach 661,531 in the worst-case scenario. However, although the number of fatal crashes may decrease in the next decade, it is forecasted to reach 11,241 within the next 10 years with the worse scenario estimated at 19,034 within the same period. At the same time, the number of persons killed in fatal crashes is also predicted to be roughly constant at 14,739 but may also reach 172,784 in the worse scenario. Overall, the present study reveals perhaps the positive effects of government initiatives to curb road crashes and their consequences; we call for more stronger actions for a drastic reduction in road accident events in South Africa.